Combined effects of environmental factors on human perception and objective performance: A review of experimental laboratory works. (24th March 2018) - Torresin, S.; Pernigotto, G.; Cappelletti, F.; Gasparella, A.
Abstract: This study reports the outcomes of a literature survey aimed at exploring how different environmental factors—that is acoustic, thermal, visual, and air quality stimuli—interact in affecting building occupants' perception and performance. Recent laboratory studies have been collected, and their methodological approaches reviewed in terms of experimental design, adopted exposures conditions, perception and performance assessment methods. Results have been summarized and compared to identify interaction patterns between environmental factors and possible practical implications for improving the design of both experimental studies and the built environment. The analysis allows highlighting limitations, potential improvements and future opportunities in this field of research, thus providing a reference for further investigations aimed at a deeper understanding, modeling, and prediction of the impacts caused by the main indoor variables on human comfort and performance.